Clinical and ultrasound features of fibrous pseudotumor of tunica vaginalis of the testis: eight cases and literature review - Yang, Jiali; Chen, Hongyan; Yan, Hualin; Zhang, Yue; Liu, Juxian (Frontiers in Oncology, 2024)
ObjectiveTo investigate the clinical and ultrasound features of fibrous pseudotumor of tunica vaginalis of the testisMethodsThe clinical and ultrasound features of fibrous pseudotumor of the tunica vaginalis diagnosed by pathology in West China Hospital of Sichuan University from 2006 to 2023 were retrospectively analyzed.ResultsThe study included 8 patients diagnosed with fibrous pseudotumor of the tunica vaginalis. The average age was 51.8 ± 17 years(range:25 to 80 years). Painless nodules or masses were present in 87.5% of cases, while 12.5% presented with painless scrotal enlargement. Ultrasound findings were as follows: Lesions were nodular in 7 cases and diffuse in 1 case (left side 50%, right side 50%). 75% involved the tunica vaginalis wall; 25% involved the epididymis with concurrent epididymitis. The tunica vaginalis wall on the affected side was significantly thicker than the contralateral side (4.58 ± 2.19 mm vs. 2.59 ± 0.48 mm, P=0.012). Hydrocele was present in 62.5% of the affected cases, poor sound transmission was noted in 62.5%, and septation was observed in 12.5%. 62.5% of cases exhibited multiple small solid nodules, with a maximum diameter ranging from 8∼19 mm. Nodules were well-circumscribed, regularly shaped and isoechoic or slightly hyperechoic. In 37.5% of cases, adjacent nodules were fused and 37.5% exhibited posterior attenuation. Punctate calcifications were present in 25% of cases. There is usually less blood flow in the lesion.ConclusionThis study demonstrates that fibrous pseudotumor of the tunica vaginalis is a rare scrotal disease affecting primarily middle-aged and elderly men. It typically presents unilaterally and carries a favorable prognosis following surgical treatment. Ultrasound commonly reveals multiple slightly hyperechoic or isoechoic solid nodules with ipsilateral thickening of the tunica vaginalis wall. In some cases, nodules may involve the epididymis, with associated epididymitis, fusion of adjacent nodules, occasional calcification, and posterior echo attenuation. Most lesions exhibit poor blood flow, and hydrocele is frequently present on the affected side. The distinct clinical and ultrasound features of the disease make non-radiative ultrasound imaging an effective tool for rapid detection, differential diagnosis, and guidance for appropriate clinical treatment.